PSP Soccer Player Emotional Intelligence Overview Padang U-17 West Sumatra - sukir; ANDRIANSYAH ANDRIANSYAH (Jurnal Indragiri Penelitian Multidisiplin, 2021)
The problem in this study is that the level of emotional intelligence of PSP Padang U-17 Football players in West Sumatra is not yet known. In sports, especially in football, someone who has intelligence alone is not enough, but must also be accompanied by emotional maturity. This study aims to describe, namely: The level of emotional intelligence of PSP Padang U-17 West Sumatra soccer players as seen from self-awareness, self-regulation, motivation, empathy, and social skills. This type of research is classified as descriptive research, with a population of all PSP Padang U-17 football players in West Sumatra with a total of 20 players. This study uses a total sampling technique with a sample of 20 players. While the data analysis using the percentage technique. The results of this study revealed that the emotional intelligence of PSP Padang U-17 West Sumetera soccer players seen from self-awareness, self-regulation, motivation, empathy, and social skills, which was at a percentage of 80% and was in very good criteria. Based on the results of the study, PSP Padang U-17 football players in West Sumatra already have very good emotions.